The Development of Student Worksheet Based on STEM Integrated Blended Learning to Improve Student's Science Argumentation Skills in the Covid-19 Pandemic Era - Mohd Zaidi Bin Amiruddin; Eka Putri Dian Nata Sari; Wadhifah Qiyyamul Lailli Arrafi'; M. Samsul Ma'arif; Setyo Admoko (Berkala Ilmiah Pendidikan Fisika, 2022)
The year 2020, until now, is a year that changes all aspects of life. The spread of Covid-19 causes changes in the order in various fields ranging from health to education. The impact of the Covid-19has made students study online using existing devices. This situation needs to be addressed with the development of learning models that follow these conditions. This study aimed to determine the validity, practicality, and effectiveness of STEM-based Blended learning worksheets developed to improve students' scientific argumentation skills. This research uses the ADDIE development model (Analysis, design, develop, implement, and evaluate), which begins with analyzing needs, making student worksheet designs, developing, conducting validation tests, conducting usage tests, and managing data. Data collection uses pretest and posttest instruments consisting of 10 multiple choice questions and five essay questions. Then it was done with the student worksheet Ohm's Law practicum. Data is analyzed using validity tests, paired T-tests to test effectiveness, and questionnaires to test practicality. This research indicates that the student worksheet that was developed was validated with the content feasibility aspect obtained is very valid criteria, the linguistic aspect obtained is very valid criteria, the presentation aspect obtained is very valid criteria, and the graphic aspect obtained is very valid criteria. The results of the practicality of the student worksheet in terms of the results of the student response questionnaires and obtained with very practical criteria. Then, the results of the effectiveness of the student worksheet in terms of the pretest and posttest treatment obtained an average N-Gain value was included in the medium category. Lastly, the student worksheet is feasible and ready to be used as teaching material. In the future, it is hoped that further research related to learning scientific argumentation to train students' argumentation skills in line with technological developments.